Stakeholder Theory Approach in Strategic Management: A Critical Review and Practical Implications - Ahmad Fuad Arrosyid; Ari Setia Nugraha; Husni Maulana (Brilliant International Journal Of Management And Tourism, 2026)
The modern business environment requires companies to adopt strategies that not only focus on maximizing shareholder profits but also emphasize value creation for all stakeholders. This article critically reviews the integration of Stakeholder Theory within strategic management, examining its alignment and potential conflicts with traditional strategic theories while exploring its practical implications. The study employs a systematic literature review combined with conceptual and critical analysis. The findings indicate that Stakeholder Theory has developed from a complementary perspective into a fundamental strategic approach for achieving sustainable competitive advantage. The analysis shows that this theory strengthens competition-based and resource-based perspectives by highlighting the importance of relational resources and shared value creation among stakeholders. Nevertheless, challenges such as the risk of superficial implementation and greenwashing require organizations to apply the theory authentically. Effective implementation can be achieved through integrated governance systems, appropriate incentive structures, and comprehensive performance measurement frameworks. Therefore, the integration of Stakeholder Theory is considered a strategic necessity, and organizations are encouraged to redesign their strategic management processes by placing stakeholder analysis at the core of decision-making and long-term planning.